Metode Syarah Hadis Perspektif Imam Al Qasthalani dalam Kitab Irsyad As-Sari Syarhi Sahih Al Bukhari: Menimbang dengan Perspektif Hermeneutika (RIWAYAH, 2015)
AbstractFiqh al-Hadith is the conceptual framework of understanding tradition, while the Syarah of tradition is operational concrete steps in writing on some books of commentary. One of the most popular books of hadith is authentic books of Bukhari. In Saheeh Bukhari, some scholars provide a good appreciation in the form of criticism, commentary (commentary) and so on. Associated with a number of books of commentary in authentic tradition of Bukhari, Mustafa Azami identifies the best commentary, there are three books including Fathu al Bari Ibn Hajar al-Asqalani, Irshad al-Sari al-Qasthalani work and Umdat al-Qari works Badruddin al-Aini. This study will focus on the book of commentary Ershad al-Sari works of Imam al-Qasthalani. Imam al-Qasthalani (851-923 H) is a scholar of hadith following Syafii. The principal issues to be examined in this study were (1) How does the method of understanding hadith developed by Imam Al Qasthalani in the book Irshad al-Sari. (2) How is the Hermeneutics overview of the method of understanding the hadith by Imam al-Qasthalani. The formulation of hadith understanding of Qasthalani in the book of hadith Imam Ershad al Sari generally using tafsili commentary. A method of understanding the commentary Ershad al Sari can be mapped on (1) Model of Hadith commentary, (2) Approach of Hadith commentary, and (3) Step of commentary specifically for each hadith in each chapter. In view of hermeneutics, a method of understanding the book of hadith Imam Qasthalani in Ershad al Sari has already implemented elements of hermeneutics as a theory in the sense of understanding approach.Keywords: Hadith Commentary (Syarah), Fiqh al-Had{i>s, Irsya>d as-Sa>ri, Al-Qasthalani, Hermeneutics